LncRNAs has been identified as regulators of Myeloid-derived suppressor cells in lung cancer - Liu, Yifan; Han, Yukun; Zhang, Yanhua; Lv, Tongtong; Peng, Xiaochun; Huang, Jinbai (Frontiers in Immunology, 2023)
Lung tumours are widespread pathological conditions that attract much attention due to their high incidence of death. The immune system contributes to the progression of these diseases, especially non-small cell lung cancer, resulting in the fast evolution of immune-targeted therapy. Myeloid-derived suppressor cells (MDSCs) have been suggested to promote the progression of cancer in the lungs by suppressing the immune response through various mechanisms. Herein, we summarized the clinical studies on lung cancer related to MDSCs. However, it is noteworthy to mention the discovery of long non-coding RNAs (lncRNAs) that had different phenotypes and could regulate MDSCs in lung cancer. Therefore, by reviewing the different phenotypes of lncRNAs and their regulation on MDSCs, we summarized the lncRNAs’ impact on the progression of lung tumours. Data highlight LncRNAs as anti-cancer agents. Hence, we aim to discuss their possibilities to inhibit tumour growth and trigger the development of immunosuppressive factors such as MDSCs in lung cancer through the regulation of lncRNAs. The ultimate purpose is to propose novel and efficient therapy methods for curing patients with lung tumours.